Cosmogenic helium signatures at Deception Island volcano (Antarctica): geochronological implications for its eruptive history - Antonio M. Álvarez-Valero; Hirochika Sumino; Ray Burgess; Lara Arribas; Antonio Polo-Sánchez; Adelina Geyer; Antonio Caracausi; Helena Albert; Meritxell Aulinas; Masao Ban; Javier Borrajo; Marcos García-Arias; et al. (Scientific Reports)
Abstract Cosmogenic nuclei production for dating the Earth surface exposure of rock/mineral samples, especially 3He, is a robust technique in geochronology. We describe its application to constrain the ages of key eruptive episodes of the volcanic history of Deception Island (Antarctica): (i) the volcanic products of the island formed before the caldera collapse (pre-caldera material); and (ii) the caldera-forming event (syn-caldera material). High 3He/4He ratios (up to 910 RA; RA = 1.39 × 10–6) in the crystal structure of olivine phenocrysts measured through total fusion He release are much higher than the magmatic values previously obtained in the inclusions of the same olivines obtained by hydraulic crushing. Such high values indicate a cosmogenic origin and reveal an age of c. 4 Ma for the pre-caldera material, and c. 4.6 ka and 170 ka for the syn-caldera deposits. The result of c. 4.6 ka for the caldera collapse episode is consistent with previous age estimations based on tephrochronology, whereas the c. 170 ka result reveals the presence of pre-caldera olivines embedded in the syn-caldera deposits that experienced less exposure to cosmic rays compared to the samples with ages of 4 Ma. This oldest age estimate represents the first quantitative geochronological approach attempting to date Deception Island formation.